EFFECTS OF PRESCRIBED BURNING ON WILD TURKEY HABITAT PREFERENCE AND NEST SITE SELECTION IN SOUTH GEORGIA - D. Clay Sisson; Dan W. Speake; J. Larry Landers; James L. Buckner (Wildlife Society Bulletin)
Abstract: Habitat preferences and nest site selections of 37 radio‐instrumented eastern wild turkeys Meleagris gallopovo silverstris were studied for 2 years on a southern Georgia area with a long history of prescribed burning. “Green‐ups” stimulated by burning in December to February were avoided by turkeys during winter, but pine‐hardwood, hardwoods, and fields of waste corn or cool‐season grasses were used. Forest openings were preferred in spring of both years. Old‐field pine plantations were preferred the first spring after planting but avoided the second spring. Freshly burned pinelands were preferred in spring 1988 but avoided the following spring when burn area extent was much larger. Annually burned pinelands were used more (P < 0.05) post‐burn than pre‐bum. Pine uplands left unburned for 1‐3 years were avoided for general travel range but were highly preferred (P < 0.01) nesting habitat. Seventeen of 23 (74%) nests were in these “roughs” averaging 2.7 ha. Site‐specific burning plans should be tailored to best suit local conditions.